2015
DOI: 10.1590/1983-1447.2015.03.45470
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic characteristics and quality of life of urban and rural elderly people with heart disease

Abstract: Objective: To compare the socioeconomic variables and quality of life scores (QOL) of elderly residents with heart diseases in urban and rural areas.Method: household survey with 829 urban and 220 rural elderlies. The data were collected using: Brazilian Questionnaire for Functional and Multidimensional Assessment, WHOQOL-BREF and WHOQOL-OLD. The collection in the urban area was from June to December of 2008 and, in the rural area, from June 2010 to March 2011. Chi-square, t-student and multiple linear regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Our study showed that subjects not using any psychopharmacological treatment, and therefore probably not displaying any comorbid mental disorders, had a significantly better QoL than subjects who did. Indeed, psychiatric drug treatment is an independent 15 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) p < 0.001…”
Section: Predictors Of Quality Of Lifementioning
confidence: 99%
See 3 more Smart Citations
“…Our study showed that subjects not using any psychopharmacological treatment, and therefore probably not displaying any comorbid mental disorders, had a significantly better QoL than subjects who did. Indeed, psychiatric drug treatment is an independent 15 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) p < 0.001…”
Section: Predictors Of Quality Of Lifementioning
confidence: 99%
“…Female population showed higher GHQ12 scores when compared to male population (14)(15)(16)(17)(18)(19) vs. 12 [IQ 9 -17], p = 0.03). Similarly, unemployed patients showed higher GHQ12 scores when compared to employed patients (15)(16)(17)(18)(19)(20) vs. [12][13][14][15][16], p < 0.00). Unemployment (OR 2.09, CI 95% 1.5 -3.0, p < 0.00), non-opioid psychopharmacological treatment (OR 1.82, CI 95% 1.3 -2.6, p = 0.00) and substitution therapy with buprenorphine (OR 0.55, CI 95% 0.3 -0.8, p = 0.01) were independent predictors of GHQ-12 >20.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Poucos estudos têm se dedicado a pesquisar os possíveis fatores relacionados à saúde de idosos do meio rural, que segundo esses autores, apresenta sinais de dificuldades no acesso aos serviços de saúde [1]. É imprescindível que sejam ampliadas políticas públicas para a melhoria da qualidade de vida na longevidade, para que tanto as sociedades desenvolvidas quanto aquelas em desenvolvimento possam atender de forma mais igualitária os idosos [2].…”
Section: Introductionunclassified